Pengaruh Kedisiplinan Peserta Didik Terhadap Hasil Belajar Kelas IV Mata Pelajaran Pendidikan Pancasila Di Sekolah Dasar - Muhammad Arie Zulfan; Misriandi Misriandi (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
This research is motivated by the low level of discipline towards students so that students experience difficulties in understanding learning and hamper students' digestibility in understanding what the teacher explains, especially in learning material. The research hypothesis is that there is an influence of student discipline on the learning outcomes of class IV elementary school students at SDN Duren Seribu 01. The aim of this research is to find out whether there is an influence of student discipline on school learning outcomes. This research was carried out at SDN Duren Seribu 01, Duren Seribu Village, Bojongsari District, Depok City. The research population used in this research was class IV B with a sample of 27 students. The instrument given is a description test with a total of 15 questions to see the students' learning results. This research was conducted with pre-experimental research using a quantitative approach. The data collection techniques used in this research were observation, tests, and documentation, then success in this research was proven by the T test with results showing 0.001 < 0.05, thus it can be concluded that there is an influence of learning discipline on learning outcomes.